TECHNOLOGIES OF PROFESSIONAL SKILLS DEVELOPMENT OF STUDENTS IN THE PROCESS OF FOREIGN LANGUAGE TEACHING - Shakhnoz Atadjanova; Madina Mirkasimova; Vasila Kushbakova; Shuxrat Akramov (The Bioscan, 2024)
This scientific article is devoted to the technology issues of developing professional skills of students of non- philological higher education institutions. In particular, in today's modern conditions of Uzbekistan, the development of professional skills of specialists in various fields of foreign language education is becoming an urgent problem. The importance of foreign language education in the development of professional skills of future foreign language teachers is highlighted in every case. In this regard, scientific research works of a number of scientists have been studied and properly analyzed.